Odoo 12 Development Cookbook - Third Edition - Gajjar, Parth; Fayolle, Alexandre; Brunn, Holger; Reis, D. (Packt Publishing, 2019)
Build customized solutions for your business using the latest features of Odoo 12 and Python Key Features Get up to speed with Odoo 12 to create custom and reusable modules Interconnect your application with other systems by implementing web APIs Understand the mechanisms powering the Odoo framework and Odoo.sh to build robust enterprises Book Description Odoo is a powerful framework known for rapid application development. Its latest release, Odoo 12, introduces tons of new features. With this book, you'll learn how to develop powerful Odoo applications from scratch, using all the latest features. This Odoo cookbook starts by covering Odoo installation and deployment on the server. Next, you'll explore the Odoo framework with real-world examples. You'll create a new Odoo module from the ground up and progress to advanced framework concepts. You'll also learn how to modify existing applications, including Point of Sale (POS). This book is not just limited to backend development; the advanced JavaScript recipes for creating new views and widgets will help you build beautiful UI elements. As you move forward, you'll gain insights into website development and become a quality Odoo developer by studying performance optimization, debugging, and automated tests. Finally, you'll learn the latest concepts like multi-website, In-App Purchasing (IAP), Odoo.sh, and IoT Box. By the end of the book, you'll have all the knowledge you need to build powerful Odoo applications. The development best practices used in this book will undoubtedly come handy when you are working with the Odoo framework. What you will learn Develop a module in the Odoo framework and modify the existing flow of any application Build dynamic websites with Odoo CMS Create and modify backend JavaScript components in Odoo and POS Connect and access any object in Odoo via Remote Procedure Calls (RPC) Illustrate the different tools available in Odoo to implement business processes for your records Implement in-app purchase services Manage, deploy, and test an Odoo instance with the PaaS Odoo.sh Configure IoT Box to add and upgrade Point of Sale (POS) hardware Who this book is for If you're a Python developer who wants to develop highly efficient business applications with the latest Odoo framework, or if you just want a solution guide for all your Odoo development issues, this book is for you. Some JavaScript programming and web development experience is necessary to get the most out of th ...
Online resource; Title from title page (viewed April 27, 2019)
Keywords: Odoo (Computer file); Application software -- Development; Enterprise resource planning; Logiciels d'application; Développement; Progiciels de gestion intégrés; Application software; Development